Strengthening the Role of Mosques for Community Economic Empowerment - Safi’i, Muhammad Aris; Shulthoni, Muhammad; Arwani, Agus; Aenurofik, Aenurofik; Darutama, Ardiyan; Kamal, M. Rikzam; Sholeh, Muhammad Hilmi (Program Studi Pengembangan Masyarakat Islam, 2025)
In the face of the complexity of socio-economic challenges in the Southeast Asian region, conventional approaches often fail to reach the most vulnerable segments of society. Therefore, an empowerment model that relies on local and spiritual strengths is needed as a foundation for sustainable and contextual change. This study aims to strengthen the role of mosques in the economic empowerment of Muslim communities in Indonesia, Malaysia, and Singapore. This program uses a community participatory approach, specifically participatory action research, which involves stages such as socialization, formation of a driving team, skills training, and support for mosque-based micro and small businesses. This empowerment uses a qualitative approach with 15 participants. The results of the study showed that this program succeeded in establishing 180 new micro businesses in three countries, increasing the skills of participants by 70% and reducing the average unemployment rate by 20%. These findings imply that mosques have substantial potential as centers of economic empowerment that can improve the welfare and economic independence of Muslim communities around mosques. This model can also be adopted by other religious institutions to support community-based economic development.